Trade and Child Labor : A General Equilibrium Analysis - Subhayu Bandyopadhyay; Sudeshna C. Bandyopadhyay (Institute for the Study of Labor (IZA), 2005)
This paper augments the existing literature on trade and child labor by exploring the effects of terms of trade changes in the context of a three good general equilibrium model, where one of the goods is a non-traded good. We find that under quasi-linear preferences the effect of the terms of trade on child labor depends critically on the pattern of substitutability (or complementarity) in the excess demand functions between the export good and the nontraded good. We extend the analysis to the case of homothetic preferences and find that the basic result is somewhat modified in a context where the marginal utility of income is affected by the terms of trade. We also extend the analysis to the case where factors move freely between the three goods as in a Heckscher-Ohlin type framework. Finally, we show that a balanced budget policy of taxing the education of skilled families and subsidizing the education of unskilled families must reduce child labor without any impact on aggregate welfare.
Keywords: F1; O19; 330; child labor; non-traded goods; substitutability or complementarity; terms of trade; Kinderarbeit; Aussenwirtschaftstheorie; Mehr-Sektoren-Modell; Nicht-handelbares Gut; Produktsubstitution; Allgemeines Gleichgewicht; Terms of Trade; Theorie